Systemic treatment policies in ovarian cancer: the next 10 years. (1st October 2003) - Biagi, J. J.; Eisenhauer, E. A.
Abstract : Over the past two decades, the development of treatment policies and practice standards has become formalized. In ovarian cancer, most attention has been focused on the development of policies for front-line systemic treatment, using survival as the major outcome that should drive change. This review summarizes the evidence that supported the emergence of paclitaxel–carboplatin as a widely used standard of care for front-line therapy and some of the contradictory data from randomized studies. Furthermore, recently completed or ongoing randomized studies of the addition of a third cytotoxic agent to paclitaxel–carboplatin are summarized. Finally, some novel noncytotoxic approaches are discussed. New standards of care and treatment policies in the next decade will be based on high-quality evidence of improved survival from controlled studies. Many such trials are now ongoing or planned.